Ein Konzept für die Einführung von ausgewählten Besonderheiten der Fachsprache in der Übung Grundlagen des deutsch-polnischen Übersetzens für Studierende der Angewandten Linguistik mit dem Schwerpunkt Translationswissenschaft - Krenz-Brzozowska, Lucyna (2022)
The article presents a concept of gradual cyclical progression of material in the practice-oriented teaching of characteristics of specialised language in translation classes for beginners, which was developed by the author for the exercise Fundamentals of German-Polish Translation. The starting point for the development of the concept was the characteristics of the specialised language named by Roelcke ([1999] 2020: 69–154) and the framework conditions of the exercise (programme of the degree course, aims of the exercise, graduate profile and the situation of translators on the translation market). Next, the concept is presented in terms of the division of material and its implementation in the class, where the gradual cyclical progression of the material covered was the highest instance, which is substantiated with examples. Since the concept owes its origin to the everyday practice of translators, the paper is based much more on the translator's own experience and reflections than on a broader analysis of the relevant literature, which is usually theoretically oriented and does not provide any concrete useful hints on how theoretical knowledge could be implemented in practice-oriented translation teaching.
Keywords: Translation; Specialised Translation; Specialised Language; Terminology; Term; Specialised Language Charateristics; Specialised Language Grammar